South Africa: The early quest for liberty and democracy - Wim A. Dreyer (HTS Teologiese Studies/Theological Studies, 2015)
The early quest for liberty and political freedom in South Africa had been influenced by various factors, inter alia political sentiments which originated in Reformed, Huguenot and Patriotten political theory. An analysis of early political ideas indicates that religious sentiments had a significant influence on the development of political ideas. These sentiments and ideas all contributed to a passionate search for freedom, justice and democracy. The different strata of religious and political ideas manifest in a continuous and discontinuous way, giving the impression of fragmented and contorted ideas, but still recognisable in terms of their origins. This contribution is an attempt to identify some of the fragmented and contorted strata of ideas which influenced the early quest for political freedom and the rejection of British colonial rule in South Africa.